Harmonisasi Pluralitas Dalam Bingkai Hukum Islam di Indonesia - A, Asriawan; K, Kurniati; M, Marilang (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Plurality in Indonesia is not a new problem, but something that has existed for a long time. Indonesia was built from a nation-state structure that cannot avoid the inevitability of diversity. History has written its reality through the form of Indonesian independence as a result of working together from the pluralistic strength of this nation. This research is a library research (Library Research) which aims to analyze the form of harmonization of plurality within the frame of Islamic law in Indonesia and the implementation of plurality within the frame of Islamic law in Indonesia. In this research, the authors used a normative approach, namely an approach with the aim of finding plurality in Indonesia, so that it is hoped that they can analyze the form of harmonization and implementation of plurality within the framework of Islamic law in Indonesia. Based on the research results, the form of harmonization of plurality within the framework of Islamic law is emphasized in QS. al-Hujurat/33. Islam does not deny plurality in society, because plurality itself is considered something that is God's law. The plurality of religions that have existed for a long time in Indonesia should be accepted by all religious adherents if we want to create a harmonious, harmonious and peaceful nation even though theology is different. In terms of implementation, it can be seen from the presence of religious tolerance in Indonesia. Recognition of religious, ethnic and racial diversity in Islamic law will create an inclusive and fair foundation for all Indonesian citizens. If the understanding and implementation of plurality within the framework of Islamic law is successfully achieved, then society will experience progress towards harmony and justice.